Germany, Poland and the Common Security and Defence Policy - Chappell, L. author. aut Link
XI, 232 p.
Keywords: A comparative analysis of an old and new EU Member State's perceptions of and contributions to EU security and defence. This book focuses on change and continuity in both countries' defence policies and where convergence and divergence has occurred. This has important implications for the EU's effectiveness as an international security actor.